PENGARUH PENGETAHUAN,PENGALAMAN SPESIFIK, DAN SELF EFFICACY TERHADAP KINERJA AUDITOR DENGAN KOMPLEKSITAS TUGAS SEBAGAI VARIABEL MODERASI - Yudhi Herliansyah (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
This study is aimed to empirically analyze the influence of knowledge, specific experience and self efficacy toward an auditor’s work performance. It also empirically analyzes the influence of those mentioned factors toward an auditor’s work performance which is moderated by the complexity of the tasks. The data is collected using quesionaires. The samples for this study are collected from 92 selected auditors. They are selected using the method of purposive sampling and they consist of senior auditors, supervisors and managers. The data is analyzed using the technique of Moderated Regression Analysis (MRA) with the assistance of SPSS 21. The results of the study show that self-efficacy affect the performance auditor with a significance level of 0.011. Moderation task complexity to the relationship Specific experience and performance auditor affect the kind of pure moderation. While the complexity of the task of moderating the relationship self-efficacy and performance auditor affect the kind of quasi moderation. Adjusted R Square value of 0.824 indicates that the variation of changes in knowledge, experience and self efficacy specific for 82.4 percent, while the remaining 27.6 percent is determined by other factors.